Pengaruh Media Pembelajaran Berbasis Kinemaster Terhadap Hasil Belajar Matematika Pada Materi Bangun Ruang Siswa Kelas V Sd Negeri 107436 Rumah Lengo T.A. 2023/2024 - Gaol, Indah Lestari Lumban; Siregar, Arifin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to see the influence of Kinemaster-based learning media on mathematics learning outcomes for classroom building materials for class V students at SD Negeri 107436 Rumah Lengo T.A. 2023/2024. This type of research is pre-experimental designs research with the form of one group pretest posttest research. The subjects of this research were 28 class V students from Negeri 107436 Rumah Lengo. The instruments used in student learning activities were previously tested to determine the validity and reliability of the tests. Instruments were given before and after providing Kinemaster learning media. The analysis technique used is the normality test and hypothesis test, namely the      t-test. Before testing the hypothesis, a prerequisite test is first carried out, namely the normality test. Based on the results of the prerequisite test calculations, the pre-test data obtained a result of 0.28, the post-test obtained a result of 0.17, which means both values are > 0.05, so it can be said that the two data are normally distributed. Next, a hypothesis test was carried out and the research results showed t-count = 11.61 and t-table = 1.67. From these data it can be seen that t-count > t-table, namely 11.61 > 1.67. This means that Ha is accepted, so there is a significant influence from the use of Kinemaster-based learning media on the mathematics learning outcomes of room building material for class V students at SD Negeri 107436 Rumah Lengo T.A. 2023/2024.